2008
DOI: 10.2139/ssrn.1164835
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Behind CO2 Emission Reduction in Transition Economies

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The literature reports that economic growth-especially in the CEE and Baltic nations-along with other factors such as corruption and political instability contribute to the depletion of natural resources without adequately compensating for the consumption of natural resources (Zugravu et al 2008). It also argues that trade openness promotes environmental quality (Dean 1992(Dean , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…The literature reports that economic growth-especially in the CEE and Baltic nations-along with other factors such as corruption and political instability contribute to the depletion of natural resources without adequately compensating for the consumption of natural resources (Zugravu et al 2008). It also argues that trade openness promotes environmental quality (Dean 1992(Dean , 2002.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the stringency of environmental policies set under decentralised regimes also depends on political centralization, measured by the strength of national level political parties (Fredriksson and Wollscheid, 2014). Zugravu et al (2008) demonstrated that increases in stringency of environmental policy led to a significant net reduction in Another study by Tamazian and Rao (2010) investigated the linkage between economic development, financial development and institutional quality on environmental degradation in transition countries using GMM (Generalised Method of Moments) for 24 transition countries from 1993-2004. The results lend support to the EKC hypothesis while also confirming the importance of both institutional quality and financial development for reducing CO2 emissions in the region.…”
Section: Review Of Relevant Literaturementioning
confidence: 99%
“…For a review of the theoretical reasoning behind the link between trade openness and emissions growth, we refer among others to Zugravu et al (2008), Frankel and Rose (2005), Cole (2003Cole ( , 2004, Cole and Elliott (2002), Dietzenbacher and Mukhopadhay (2006) and . The sign of the relationship depends on two potentially conflicting forces: the delocalisation of polluting industries into less developed areas with lax regulation (pollution haven effect) and the country specialisation in capital intensive and energy intensive industrial sectors (factor endowment effect).…”
Section: Ekc Oriented Specificationsmentioning
confidence: 99%